PROFILE OF NEURAL TUBE DEFECT IN RSUD Dr. SOETOMO, 2013-2018 - Mohammad Nata Ardiansyah; Muhammad Arifin Parenrengi; Prastiya Indra Gunawan; Wihasto Suryaningtyas (Universitas Airlangga, 2022)
Background: Congenital abnormalities are structural growth abnormalities that have arisen since the intrauterine life caused by many factors, including genetics, pregnancy nutrition, infection, and social status. Purpose: This study aims to observe the clinical profile of Neural Tube Defect (NTD) patients in Dr. Soetomo Hospital from 2013 to 2018. Methods: This research was a descriptive study using secondary data from medical records from September 2013 to March 2018 to determine the profile of NTDs. The inclusion criteria for this study were patients aged 1-14 years diagnosed with NTD. Variables observed included gender, age, primary diagnosis, natal history, nutritional status, history of past therapy, referral status, comorbidities, and outputs. Data analysis was conducted in a descriptive method and presented in tables and diagrams. Results: This study found that out of 232 samples, 122 were female and 110 were male. Spina bifida unspecified was the most common diagnosis in 80 patients (32.78%), then encephalocele unspecified, 50 (20.49%), encephalocele anterior, 31 (12.44%), Myelomeningocele (MMC), 25 (10.24%), encephalocele unspecified, 23 (9.42%), and lipomyelocele, 20 (8.19%). There was 244 diagnosis found with 12 dual diagnoses. Works done depend on the clinical and nutritional condition of the patient. Patients with NTD tend to need more nutrition. Most NTD patients present with comorbidities, and the most common one is hydrocephalus. Many NTD patients had unknown treatment output. Most patients were still in outpatient care for further supervision. Conclusion: NTD incidence rate in RSUD Dr. Soetomo 2013-2018 is still relatively high.